2019
DOI: 10.5603/fm.a2019.0009
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography measurement of the bone matrix of vertebral pedicle and its clinical significance

Abstract: Background: To provide the anatomic basis for the clinical application of the transpedicular screw fixation. Materials and methods: Thirty spine (C 2-L 5) specimens were used. The width of the pedicle cortex and width of the pedicle medullary cavity (WPC and WPMC), and the height of the pedicle cortex and height of the pedicle medullary cavity (HPC and HPMC) were measured at the isthmus of the pedicle using computed tomography (CT) scanning. Results: Width of the pedicle medullary cavity changed in a three-dov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…In studies evaluating pedicle diameters, many find the C4 pedicle diameter is wider than the C3 pedicle diameter, 14,15,18,28 and many find the C3 pedicle diameter to be larger than the C4 pedicle diameter 17,19 . However, almost all studies examining the medial pedicle angle found the C4 medial angle to be greater than the C3 medial angle 7,12,14,15,17,18,28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies evaluating pedicle diameters, many find the C4 pedicle diameter is wider than the C3 pedicle diameter, 14,15,18,28 and many find the C3 pedicle diameter to be larger than the C4 pedicle diameter 17,19 . However, almost all studies examining the medial pedicle angle found the C4 medial angle to be greater than the C3 medial angle 7,12,14,15,17,18,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In studies evaluating pedicle diameters, many find the C4 pedicle diameter is wider than the C3 pedicle diameter, 14,15,18,28 and many find the C3 pedicle diameter to be larger than the C4 pedicle diameter. 17,19 However, almost all studies examining the medial pedicle angle found the C4 medial angle to be greater than the C3 medial angle. 7,12,14,15,17,18,28,29 Although the lateral devi- ation of C4 pedicle screws is higher than that of C3 screws, the lack of a difference between the medial deviations suggests that the high rate of deviation in C4 pedicle screws is due to the wide medial angle of the pedicles rather than their thinness.…”
Section: Deviationsmentioning
confidence: 99%
See 1 more Smart Citation